Isabel Lousada, perfil para uma pioneira:Adelaide Cabete (1867-1935), Lisboa, Fonte da Palavra e Associação Cedro, 2017, 179 pp., ISBN: 978-989-667-047-4 - Baltazar, isabel (Historiæ, 2018)
Não possui